Advances in Cryogenic Engineering Materials 1994
DOI: 10.1007/978-1-4757-9053-5_154
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic Fracture Behavior of 316LN in Magnetic Fields up to 14.6 T

Abstract: Some of the proposed magnet case alloys for the International Thermonuclear Experimental Reactor (ITER) are metastable austenitic stainless steels. The case will be subjected to high loads and can be as much as 100 mm thick. Case assembly will probably require thick section welding with its attendant chemical inhomogeneity. Even alloys that are thermally stable with respect to martensitic transformation can, under these conditions of high stresses, cryogenic temperature, and high magnetic fields, undergo trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…It has been suggested that EL and RA are influenced by the slight difference in the chemical composition of the weld metal, welding method and welding conditions. [15], c [16], d-l [17], m [18], n [19] o [20], p [21], q,r [22], s [23], t,u [24], v [25], and w [26], respectively. Figure 4 shows a plot of C+N content on the horizontal axis and σ 0.2 and σ B on the vertical axis at 4.2 K. To check if there is a correlation between them and the C+N content, the approximate equations were added to figure 4 and the R 2 of each was evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that EL and RA are influenced by the slight difference in the chemical composition of the weld metal, welding method and welding conditions. [15], c [16], d-l [17], m [18], n [19] o [20], p [21], q,r [22], s [23], t,u [24], v [25], and w [26], respectively. Figure 4 shows a plot of C+N content on the horizontal axis and σ 0.2 and σ B on the vertical axis at 4.2 K. To check if there is a correlation between them and the C+N content, the approximate equations were added to figure 4 and the R 2 of each was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The reference data in this report are those reported for type 304L [8][9][10][11][12][13], 316L [8,9,14,15], and 316LN [13,[15][16][17][18][19][20][21][22][23][24][25][26] base materials and for weldments using type 304L [9,16,[27][28][29][30], 316L [9,16,[27][28][29]31], and 316LN [16,32,33] base materials for tensile properties, fracture toughness, or both at cryogenic temperatures. The base materials have a low carbon content (approximately 0.05 mass%) to suppress intergranular precipitation of chromium carbides and to ensure strength and toughness at low temperatures.…”
Section: Materials and Test Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The general trend is that the fracture toughness decreases as the yield strength of the material increases, the data obtained in this paper being in reasonable qualitative agreement with the experiments taken from the literature. Murase et al (1993), Nyilas and Mitterbacher (2010), Chan et al (1994), Drexler et al (1994), Krauth and Nyilas (1980), Mazandarany et al (1980), Muster and Elster (1990), Nyilas and Yanagi (1989) and Ogata et al (1992).…”
Section: Discussionmentioning
confidence: 99%
“…When the test is carried out under such a condition as the martenSltIc transformation is suppressed, the magnetic effect on fracture toughness disappears. 2 ,3 Under suitable conditions, an increase in fracture toughness was observed 3 by an application of high magnetic fields.…”
Section: Introductionmentioning
confidence: 95%